GLOBAL FUTURES key concepts for social transformation. - Munck, Ronaldo (ROUTLEDGE, 2025)
Global Futures: Key Concepts for Social Transformation provokes us to rethink some of the key words and concepts which define the current global order. Prompted by crises around the world, it seeks to re-energise our desire for a better future.The book takes seven key concepts from the new global studies and considers how they are used and whether they are adequate for addressing the twenty-first century's increasingly complex global order. The topics covered include widely used concepts such as development, modernity, history, and politics, as well as more unusual themes such as desire, complexity, and alternative futures. The core message of this book is that we need to grasp the complex and contradictory reality behind these important concepts in order to foster a new way of thinking, seeing, and acting for a future fit for human purpose.Written by Ronaldo Munck, a key social theorist and social activist with a Latin American and European background, this book will be perfect for students and researchers of sociology, politics, international relations, and global development.
Keywords: Globalization.; International relations.; elektronické knihy; electronic books